Water Quality Assessment Klang River Water Treatment Plants - Mohiyaden, HA; Sidek, LM; Hayder, G; Noh, MN (International Journal of Engineering and Technology, 2018)
The quality of Klang river water is deteriorating dramatically since it is in urban places every day and become one of the major problems.Â Therefore, the Malaysian government had initiated one river cleaning project named River of Life (ROL) project. This project is for rehabilitating and restoring the Klang river. A series of river water treatment plant (RWTP)s have been operated in Klang river catchment since 2014. Six RWTPs station has been monitored up to eight stations until presents. Eight parameters consisting of physio-chemical types and biological types have been recorded. RWTP effluent discharges are targeted to achieve Malaysia Interim National Water Quality Standard (INWQS) under Class II B. Since previous RWTP performance only emphasized on local river pollutants and certain conditions, this paper will investigate the effectiveness of full-scale RWTP unit process for river condition. Water quality assessment are involved which are consist of effluent water quality monitoring and pollutant removal efficiency. Most of the major pollutants able to be reduced by more than 50% reduction. Although BOD and AN still not able to achieve standard range gazetted by INWQS Class IIB, there is an improvement of river water quality at Klang River by using IFAS technology adopted in the RWTP system.